Optimization of production methods for gallium-68 PET radiopharmaceuticals in a hospital radiopharmacy - Le Roux, Johannes Stephanus (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.